PELAKSANAAN PENYULUHAN AGAMA DAN PEMBANGUNAN OLEH PENYULUH AGAMA DI KOT DENPASAR BALI - Abdul jamil (Jurnal Dialog, 2014)
As the capital city of Bali province and as the main tourist destination, Denpasar serves as the most visited city with sustainable regional budget (APBD). It has been evidence that foreign cultures as part of globalization effect of tourism did not contribute positively to the development of the region. These foreign cultures have been indicated as a negative force to the locals, either on economic, social, or cultural aspects. This paper explores the attempts of the local government, particularly the Office of Religious Affairs of Denpasar in improving the competence of religious communicators as stipulated in the Act of Kepmenkowasbangpan No. 54 / KEP / MK.WASPAN / 9/1999. Similarly, it also presents how these communicators performed their religious communication services amidst the rapid cultural change in Bali.